2014
DOI: 10.1155/2014/584934
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Pathway in the Treatment of Nocardial Brain Abscesses following Systemic Infections

Abstract: Nocardial infections are commonly encountered in patients with immunocompromised states. Cerebral nocardiosis is an uncommon clinical entity, representing only 2% of all cerebral abscesses. It has a higher mortality rate, especially for multiple cerebral lesions in immunocompromised hosts following systemic infections. However, an optimal treatment policy to deal with these immunocompromised patients in Asia is still lacking. We retrospectively reviewed the subjects with nocardial brain abscesses from 2001 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 28 publications
(36 reference statements)
0
14
0
7
Order By: Relevance
“…Several cases of isolated brain abscess have been reported in the literature, but often with poor information on radiological staging. [24][25][26] The strategy for radiological staging was unfortunately heterogeneous and depended on the medical staff. In visceral nocardiosis, especially in immunocompromised patients, a systematic examination including blood cultures, CAP-CT, and head CT should be performed.…”
Section: Discussionmentioning
confidence: 99%
“…Several cases of isolated brain abscess have been reported in the literature, but often with poor information on radiological staging. [24][25][26] The strategy for radiological staging was unfortunately heterogeneous and depended on the medical staff. In visceral nocardiosis, especially in immunocompromised patients, a systematic examination including blood cultures, CAP-CT, and head CT should be performed.…”
Section: Discussionmentioning
confidence: 99%
“…Nocardiosis of the central nervous system is a rare cause of cerebral abscesses, accounting for only approximately 2% or 30 to 50 annual cases 7 . The subject in this case carried several risk factors for Nocardia brain abscess, including long-term corticosteroid therapy, chemotherapy-induced leukopenia, and previous brain pathology.…”
Section: Discussionmentioning
confidence: 83%
“…Nocardiosis of the central nervous system is a rare cause of cerebral abscesses, accounting for only approximately 2% or 30 to 50 annual cases. 7 The subject in this case carried several risk factors for Nocardia brain abscess, including long-term corticosteroid therapy, chemotherapy-induced leukopenia, and previous brain pathology. Clinical diagnosis is difficult because the presentation mimics other brain pathology and classic signs and symptoms of infection (ie, fever) are often hidden in immunocompromised patients.…”
Section: Discussionmentioning
confidence: 88%
“…Ninan et al [32], 2016 South India 131 cases: N. asteroides (73), Nocardia spp. (32), N. brasiliensis (2), aerobic actinomycetes (24) Skin (36), eye (36), pulmonary (35), immunosuppressive therapy (48) Nampoory et al [47], 1996 Kuwait 6 cases: N. asteroides (4), N. otitidiscaviarum (1), N. farcinica (1) Pulmonary nocardiosis (3: with 2 cerebral abscess, 1 meningitis); perinephric abscess (1), thigh abscess (1), ischiorectal abscess (1) Lai et al [65], 2011 Taiwan 138 isolates: N. brasiliensis (58), N. cyriacigeorgica (22), N. farcinica (11), N. beijingensis (8), N. otitidiscaviarum (7), N. nova (6), N. puris (6), N. asiatica (5), N. flavorosea (5), N. abscessus (3), others 7Skin and soft-tissue, respiratory tract specimens, brain biopsy, blood, lymph node…”
Section: Casesmentioning
confidence: 99%
“…For CNS nocardiosis, based on recommendations by various authors [73][74][75], it can be concluded that for clinically stable patients with a brain abscess < 2 cm, treatment should be initiated with a long-term antibiotic, initially intravenously for 4-6 weeks followed by oral therapy for 6-12 months with or without aspiration of abscess. Aspiration helps to relieve mass effect and aid in definitive laboratory diagnosis.…”
Section: Treatment Of Nocardiosismentioning
confidence: 99%